2023
DOI: 10.1002/chem.202301473
|View full text |Cite
|
Sign up to set email alerts
|

Strong Be−N Interaction Induced Complementary Chemical Tuning to Design a Dual‐gated Single Molecule Junction

Abstract: The interaction between pyridines and the π‐hole of BeH2 leads to the formation of strong beryllium‐bonded complexes. Theoretical investigations demonstrate that the Be‐‐‐N bonding interaction can effectively regulate the electronic current through a molecular junction. The electronic conductance exhibits distinct switching behavior depending on the substituent groups at the para position of pyridine, highlighting the role of Be‐‐‐N interaction as a potent chemical gate in the proposed device. The complexes ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…These findings provide insight into the deliberate modulation of spin-dependent electronic transport properties using light-active AZB chromophores within these molecular junctions. Moreover, they underscore the critical role played by quantum effects in phenomena associated with zero-bias electronic transport …”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…These findings provide insight into the deliberate modulation of spin-dependent electronic transport properties using light-active AZB chromophores within these molecular junctions. Moreover, they underscore the critical role played by quantum effects in phenomena associated with zero-bias electronic transport …”
Section: Resultsmentioning
confidence: 98%
“…Moreover, they underscore the critical role played by quantum effects in phenomena associated with zero-bias electronic transport. 89 In the meantime, there is an increase in electronic conduction within the low-bias range, which indicates the substantial influence of Kondo-type resonance on enhancing electronic conduction 90 in the molecular junction featuring the trans-AZB system. The phenomenon known as the Kondo effect is fundamentally driven by exchange-coupling interactions occurring between a localized magnetic center (or spindensity) and incoming electrons from the source electrode.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Another interesting theoretical study was performed in our group, where strong beryllium-bonded complexes were found to form from the interaction between parasubstituted pyridines (X-Pyr), and the π-hole of BeH 2 . [31] It was observed that X-Pyr.BeH 2 complexes could be used as dualgated SMJ. The study paves the way for the development and fabrication of multifunctional single-molecule devices in the nanoscale regime.…”
Section: Non-covalent Interactions Induced Quantum Transport In Singl...mentioning
confidence: 99%
“…Furthermore, the computationally very cheap ωB97X-3c/vDZP method performs comparably to the “traditional” DC DFT approaches and is, thus, suitable for a cost-effective screening of the potential energy surfaces. These findings are expected to be useful in the modeling of supramolecular junctions and other complex systems [ 39 ].…”
Section: Introductionmentioning
confidence: 99%